Comprensión crítica en jóvenes de Bolivia, Colombia y Ecuador. - PORTUGAL ESCOBAR, Rigliana; DÁVILA-NAVARRO, Édgar; MORILLO PUENTE, Solbey; RÍOS HERNÁNDEZ, Iván Neftalí (Chasqui (13901079))
The media facilitate the processes of socialisation, in a context where interactivity and digitalisation are advancing at a dizzying pace, and where citizens need to develop competences that promote the exercise of rights with responsibility and autonomy. Critical understanding, a dimension of media competence, is based on awareness and corresponds to critical thinking. The research presents the results of the application of a questionnaire to 2158 young network users in Bolivia, Colombia and Ecuador. The aim was to explore critical comprehension and focused on the skills of reading, comprehension and evaluation. Young people have developed critical comprehension, with autonomy, which shows their own reading and re-signification of the media. It is a priority to critically enhance the content that young people receive and produce, together with teachers who have access to training in media education, for a transformative and comprehensive educational process.